Investigating Vatican II: Its Theologians, Ecumenical Turn, and Biblical Commitment - Tanner, Norman (Asian Horizons, 2018)
Jared Wicks, Investigating Vatican II: Its Theologians, Ecumenical Turn, and Biblical Commitment, Washington DC: The Catholic University of America Press, 2018. Paperback, Pages: vii + 289. ISBN 9780813230474